1976
DOI: 10.1507/endocrj1954.23.183
|View full text |Cite
|
Sign up to set email alerts
|

Immunological studies on LATS-immunoglobulin by the reaction with staphylococcal protein A.

Abstract: The reaction of LATS activity with Staphylococcal Protein A, a specific binding protein with the Fc part of human IgG(1), IgG(2) and Ig(4), was examined. When IgG(1), IgG(2) and Ig(4) subclasses were removed from LATS positive sera or LATS-IgG fractions by affinity chromatography on Protein A-Sepharose, LATS activity decreased. Almost all LATS activity was found in the fraction that reacted with Protein A. It is suggested that LATS has an expression of a very distinct immunoglobulin G structure, and that LATS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Protein A method [23]. TSAb-IgG was applied to the affinity column (1.5 X5 cm) and incubated 30 min.…”
Section: ) Neutralization Of Tbii and Tsab Activity By Human Anti-anmentioning
confidence: 99%
“…Protein A method [23]. TSAb-IgG was applied to the affinity column (1.5 X5 cm) and incubated 30 min.…”
Section: ) Neutralization Of Tbii and Tsab Activity By Human Anti-anmentioning
confidence: 99%
“…In a previous experiment, we reported that LATS activity was dis¬ tributed in the fraction containing the 3 subclasses, IgG(l), IgG(2) and LG(4) (Ochi et al 1976). The present paper examines the separation of LATSimmunoglobulin from LATS positive serum using affinity chromatography on Anti-IgG, Anti-Fab, Anti-Fc, and Staphylococcal Protein A bound Sepharose, and the immunological properties of the biologically active fragment in LATSimmunoglobulin after hydrolysis.…”
mentioning
confidence: 92%
“…TSAb-IgG (by Protein A method [14]) was purified from other Graves’ serum with high TSAb activities. The crude IgG obtained by PEG 13.5% precipitated fraction (PF) from serum (0.2 ml) of patients with both anti-bTSH antibody and no TSAb activity was dissolved with modified Hanks’ buffer (TSAb kit).…”
Section: Methodsmentioning
confidence: 99%
“…All fractions which had been lyophilized after dialysis against distilled water for 3 days at 5°C were used for TSAb assay. An F(ab′) 2 fragment from other Graves’ TSAb-IgG was obtained from pepsin-digested TSAb-IgG using Protein A-Sepharose as previously reported [14, 15]and was affinity-purified.…”
Section: Methodsmentioning
confidence: 99%